Keberagaman Fungsi Dan Makna Nilai Estetika Dalam Rangkaian Kerajinan Sulam Di Kampung Sunan Palembang - Aji Windu Viatra; Verano, Dwi Asa Verano; Pandu Risky Pratama (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
Thread embroidery is one of the techniques for decorating fabrics using gold thread with motifs adapted to the local area, such as in Kampung Sunan Palembang. The art of embroidery crafts in Kampung Sunan Palembang shows that this embroidery is not just a textile artwork, but a cultural heritage rich in meaning and function. Embroidered decorative products function as decoration, one of which is on traditional wedding clothes, household furniture decorations, and wall decorations. The purpose of the study is to describe the variety of embroidery motif decorations, meaning values, and aesthetic functions in the results of Kampung Sunan embroidery products. This research method uses a qualitative descriptive approach. Data were collected through observation, interviews, and documentation. The results of this study found a variety of embroidery motifs, namely tendrils, boards, slanted fans, straight fans, nutmeg seeds, centipede nails, five-finger boards, flowers, and birds, meaningful values that describe social relations reflecting local identity, markers of customs as status symbols, media for inheriting women's values, and tools for uniting communities through collective practices and hereditary traditions. The function is a relationship between the work and the use of objects that are designed effectively, by criteria set based on their usefulness and efficiency, both in terms of appearance and market needs and as a creative result that can be used practically in everyday life. This research is expected to be able to provide a significant contribution in understanding the various functions and meanings of aesthetic values in embroidered cloth products in Kampung Sulaman Angkinan Palembang, and become a reference for further studies related to traditional crafts in Indonesia, especially craft arts in South Sumatra.